Filters Effect on Image Quality of 177Lu-DOTATATE SPECT Images for Neuro-Endocrine Tumors Scanning - Hussein Dakhil; Mohammad Reza Deevband; Mahasti Amoui; Ahmad Mostaar; Mahdi Ghorbani; Mohsen Khosroabadi; Mohammad Ali Ghodsirad (Frontiers in Biomedical Technologies)
Purpose: The quality of the image in SPECT scans depends on the imaging parameters which are determined experimentally in the field of nuclear medicine. Designing a dedicated scanning parameter for 177Lu-DOTATATE SPECT images is required to optimize reconstruction. Therefore, this study aims to evaluate the effect of different filters on image quality for bone SPECT scanning using 177Lu-DOTATATE.